PATTERN OF ANTIBIOTIC SENSITIVITY IN TYPHOID FEVER PATIENTS WITH POSITIVE BLOOD CULTURE: AN OBSERVATIONAL STUDY - KHAN , Z; KHAN , AM; BASIT , A; KHAN , MA; ALI , A (Biological and Clinical Sciences Research Journal, 2024)
Salmonella typhi is a type of bacteria that can cause typhoid fever, a severe infection that primarily affects people in developing countries. It is a significant public health concern. An antibiogram test was conducted by the Department of Medicine at MTI, LRH Peshawar, to test antibiotic susceptibility in samples that tested positive for typhoid culture from January 2023 to July 2023. The Kirby-Bauer disk diffusion method was used to evaluate the antibiotic susceptibility of Salmonella isolates on Mueller-Hinton agar. IBM SPSS version 22 was used to analyze all of the data. In total, 90 people participated in the research, with 40 percent being female and 50 percent male. Of the Salmonella isolates, 08 (28.20%) were sensitive to typhoid, 18 (68.80%) were MDR, and 01 (04%) were XDR. Of the 27 isolates, 6 (21.40%) showed Ampicillin sensitivity, while 21 (81.40%) showed resistance to the antibiotic. 90.20% of the isolates were resistant to chloramphenicol, while 15.60% were susceptible. 60.20% of the isolates were resistant to ceftriaxone, while 41.40% showed sensitivity to the drug. Nine isolates (30.40%) showed sensitivity to ciprofloxacin, while eighteen isolates (68.40%) showed resistance. 26 27 isolates (91.40%) showed sensitivity to azithromycin, while 01 (02.40%) showed resistance. Meropenem was the most effective antibiotic, with 100% of the isolates exhibiting Meropenem sensitivity. Based on the findings, azithromycin and meropenem are the most effective antibiotics against isolates of Salmonella spp. MDR and XDR strains of enteric fever are on the rise and exhibit a high degree of resistance to commonly prescribed medications. Antibiotic use without a prescription should be minimized, and prescribing practices should be modified.